WORK LIFE BALANCE: A STUDY ON UNIVERSITY FACULTY OF SRI PADMAVATHI MAHILA VISVAVIDYALAYAM, TIRUPATI - B.VIJAYALAKSHMI & G. LATHA (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
This paper is about the ‘work–life balance’ issues that affect faculty working in SRI PADMAVATHI MAHILA VISVAVIDYALAYAM, Tirupati. It is concerned with those factors that influence faculty ability to achieve harmony between their preferred contribution to Teaching, Research on one side of the balance, and with their roles, responsibilities and activities in private life on the other. In this paper, Faculty was defined as those working as Assistant professors, Associate Professors and Professors in Sri Padmavathi Mahila Visvavidyalayam, Tirupati. The objective of this research is to study the work life balance and to study the stressors faced by faculty in Sri Padmavathi Mahila Visvavidyalayam, Tirupati. It also attempts to study the factors that contribute to satisfaction and factors that detract from satisfaction on career progression. The research was conducted among faculty members with Reference to Sri Padmavathi Mahila Visvavidyalayam, Tirupati. Work life balance entails attaining equilibrium between professional work and other activities, so that it reduces friction between official and domestic life. Work life balance enhances efficiency and thus, the productivity of an employee increases. The findings of this study reveal the majority of the faculty members feel comfortable in their work place irrespective of their minor personal and work place irritants. The Primary data was collected through questionnaire survey and analyzed with the help of various statistical tools. This paper attempts to identify the various factor which helps to maintain work life balance among faculty employees in Sri Padmavathi Mahila Visvavidyalayam, Tirupati.